Electoral support for candidates involved in drug trafficking: experimental evidence from Peru - Ramírez Bustamante, Mariana V. (Comparative political studies, 2025)
Why do citizens vote for candidates involved in organized crime? Drawing on theories of voting behavior and accountability, I assess the extent to which individuals engage in trade-off evaluations when voting for candidates linked to drug trafficking organizations (DTOs). Using a vignette experiment embedded in online surveys in Peru, I manipulated side benefits that accrue from drug trafficking. The results, which I also test using qualitative evidence from in-depth elite interviews, show support for my core hypothesis, which I term a competence mechanism: citizens are more favorable toward DTO-linked candidates when that connection brings positive returns. Specifically, I find security side benefits increase electoral support for narco-linked politicians, while economic goods do not have a direct significant effect on voting behavior unless citizens justify this illegal economy. Further, tolerance toward the drug trade has a direct effect on support for this type of malfeasant candidates.
Online veröffentlicht am 29. September 2025
Gesehen am 16.01.2026